1995
DOI: 10.1029/95gl00798
|View full text |Cite
|
Sign up to set email alerts
|

Nonsphericity of dust‐like tropospheric aerosols: Implications for aerosol remote sensing and climate modeling

Abstract: The nonsphericity of dust‐like tropospheric aerosols causes us to question the applicability of using conventional Mie theory to compute their radiative properties. In this paper we compare T‐matrix computations of light scattering by polydispersions of randomly oriented nonspherical aerosols and Mie computations for equivalent spheres. We demonstrate that even moderate nonsphericity results in substantial errors in the retrieved aerosol optical thickness if satellite reflectance measurements are analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(143 citation statements)
references
References 19 publications
5
137
0
Order By: Relevance
“…Indeed, author's performed optical calculations by using mixtures of oblate and prolate spheroids and concluded that difference in SSA and g are lower than 10%. This result is in accordance with those reported by Mishchenko et al (1995) and Bellouin et al (2004).…”
Section: Radiative Effect Parametrization and Dust Optical Propertiessupporting
confidence: 83%
“…Indeed, author's performed optical calculations by using mixtures of oblate and prolate spheroids and concluded that difference in SSA and g are lower than 10%. This result is in accordance with those reported by Mishchenko et al (1995) and Bellouin et al (2004).…”
Section: Radiative Effect Parametrization and Dust Optical Propertiessupporting
confidence: 83%
“…For τ , reliable remote sensing measurements are often available, whereas g and ω are typically simulated by use of the SPA in conjunction with additional information on the aerosol size distribution and refractive index. Several studies have confirmed that ω is insensitive to particle shape (Mishchenko et al, 1995(Mishchenko et al, , 1997Kahnert et al, 2002;Nousiainen and Vermeulen, 2003;Kahnert, 2004), whereas it strongly depends on m. Earlier investigations concluded that g can be modelled by the SPA (Mishchenko et al, 1995), which would justify the use of the SPA in climate forcing simulations. However, recent investigations indicate that the earlier models may have underestimated the impact of aerosol non-sphericity (Kahnert et al, 2005), and that the error in g caused by the SPA can equal that related to the uncertainty in m (Kahnert and Nousiainen, 2006b).…”
Section: Introductionmentioning
confidence: 94%
“…The uncertainty in the refractive index m and, to a lesser extent, the uncertainty in the size distribution of the aerosols are commonly regarded as the most important sources of error (Myhre and Stordal, 2001). It has been generally assumed that computing the aerosols' optical properties using the Mie theory for spherical particles -henceforth referred to as the spherical particle approximation (SPA) -causes negligible errors in radiative forcing simulations (Mishchenko et al, 1995). The validity of this notion is re-evaluated in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative way, which we followed in this paper, is to use the equations derived by Middleton [1952] For each of the three approximations, a different approach is followed to calculate the particle phase functions. In the homogeneous sphere case, a simple-stable iterative scheme is used to calculate the appropriate Ricatti-Bessel functions and then the formation of the amplitude functions and of the phase function [Kerker, 1969 [Mishchenko, 1991[Mishchenko, , 1993Mishchenko et al, 1995Mishchenko et al, , 1996] to allow computations for large particles. NEPH3 uses this improved version of the Tmatrix method to calculate the phase functions of randomly oriented oblate and prolate spheroids.…”
Section: Dustmentioning
confidence: 99%